Perhitungan Struktur Aman terhadap Gempa Gedung Hotel Nunusaku di wilayah Kota Ambon - Yulius Sovian Pesung; Vector R. R Hutubessy; Herry Henry Roberth (KOLONI, 2025)
The writing of this final project aims to obtain the strength of the building structure that is safe against earthquakes, with a large magnitude force. Based on the title "Calculation of Safe Structures Against Earthquakes, Nunusaku Hotel Building in the Ambon City Area" which aims to ensure that the building can survive and remain intact in the event of an earthquake. The author himself made a building plan with the help of SAP2000v.21 structural analysis software. By using SNI 1726-2019 and SNI 1727-2020. Based on the results of the structural analysis, the column dimensions are 450 mm x 450 mm and the beams of X Direction (300 mm x 600 mm) and Y Direction (200 mm x 400 mm) for Floors 1-4. And for the detection of all loads based on the function of the hotel building that is based on the applicable SNI based on the internal forces obtained from SAP2000v.21, then for the beam reinforcement obtained on the 1st floor: X →(161,204kNm) Pedestal 8D16/4D16, (232,467) Field 5D16/3D16, Y→(32,133kNm) 3D16/2D16 (60,694kNm) Field 3D16/2D16, Floor 2: X→( 159,7445kNm) Pedestal 8D16/4D16 (227,288kNm) Field 5D16/3D16, → Y(32,152kNm) focus 3D16/2D16 (58,696kNm) 3D16/2D16 field, 3rd Floor: X→(160,956kNm) 4D16/2D16 (209,775kNm) 5D16/3D16 field, Y→(32,261kNm) 3D16/216 (58,455kNm) 3D16/2D16 field, 4th Floor: X→(102,475kNm) 4D16/2D16 platform, (105.51kNm) 4D16/2D16 field, Y→(14,2907kNm) 2D16/2D16 platform, (30,289kNm) 2D16/2D16 field, 3D16/2D16 child beam for each floor. And for the column, it is able to withstand the axial force of sebsar (1627.469kN) and Moment (117.7022kNm) of 3D19 reinforcement for each floor.